Power and Democracy through Self Governance: Negotiating Landscapes and Minefields in One Adult Education Doctoral Program - Dianne Romdeholl; Mansur Abdullah; Tania Giordani; Tom Heaney; Wendy Yanow (Adult Education Research Conference, 2008)
In this paper four graduates and a faculty member critically analyze efforts to develop and sustain democratic practice in the context of their doctoral program in higher education.
Keywords: critical pedagogy; critical theory/critical race theory; adult education